Symmetry and asymmetry as a physical and perceptual feature of the complementary pair of bearing sinusoids. Part II. Pitch matching experiments - RUTKOWSKI, L.; WICHER, A. (Archives of Acoustics, 1998)
Two experiments were designed and performed in that the pitch of complementary pairs of beats signals, referred to as SL and SH, was evaluated. In experiment 1, the changeable signal consists of a pair of signals of equal sound pressure level and of the same separation of frequencies as this between SL and SH. Experiment 2 was made in the AM mode with a changeable signal whose amplitude envelope is identical with that of the SL/SH pair; the carrier frequency could be varied during the experiment. The results of the experiment 1 do not confirm the asymmetry in the evaluation of the pitch of the pairs of SL/SH signals with respect to the average frequency of the beats, a feature that has been reported earlier in the literature. On the order hand, the outcome of the experiment 2 point to certain asymmetry, moreover, the data reveal a large pitch difference of the SL/SH pairs; this difference (for which no explanation has been offered yet) is often much larger than that measured in experiment 1. The observed asymmetry, which is due to frequency variations determined with the frequency envelope (Part I) resulting from the broadband character of the beatings, does not quite justify the range of asymmetries reported in literature.